An overview of web development for digital archive of Malaysian cultural heritage / Noor Hayati Ismail ... [et al.] - Ismail, Noor Hayati; Rashidi, Nur Aisyah Safwa; Abdul Latip, Nurul Syala; Norwawi, Norita (Universiti Teknologi MARA, Perak, 2023)
With modernization, historical structures are threatened by extinction. Preservation efforts are made, but eventually, maintaining the drawing’s physical form is no longer manageable. Hence, digital archiving is the best solution to preserve data. The research approach is a design-based study that aims at data collection and analysis of website development while reviewing many aspects of digital archiving in architectural heritage. The methods involved data compilation, sustainable digital archive development, and the arrangement of data digitally. Documentation of heritage digital archive model development is made to ensure the data of building a sustainable archive is available for future reference.